In-Situ Current Speed Measurement and Sediment Characteristics at UPNM Lake - Rahman, Ainul; Muda, Wan Baderul Hisan Wan; Rosly, Afiqah; Azzeri, Mohd; Isnan, Sarah; Aziz, Adenen; Muhamad, Siti Nur; Ahmad, Mohd Arif; Amir, Mohamad Abu Ubaidah (International Journal of Engineering and Technology, 2018)
This paper focuses on a hydrographic survey conducted at Universiti Pertahanan Nasional Malaysia (UPNM) Lake. The aim is to measure the current speed and sediment characteristics due to the limitation of information and references regarding on UPNM Lake. The hydrographic survey conducted is essential as it is the first survey carried out and indirectly outlines and provides details of the lake for future applications. All the information from the survey is prominent seeing that UPNM Lake is constantly used for either research activities, fishing activities, recreational activities by students and as a training ground for military cadets.Â The outcome gathered from this research is an analysis of data for in-situ current speed and direction at 26 designated locations (23 locations for bottom current) in the lake area and also sediment characteristics. Current speed distribution at UPNM Lake shows 80% current speed recorded in between 0.02 m/s to 0.5 m/s with the highest current speed was recorded at the magnitude of 0.68 m/s and the lowest current speed is at magnitude 0.02 m/s. For sediment characteristics, all sampling stations show mud sediment with few stations show different types of mud. The study of this water body either in physical or chemical aspect is performed to derive a better understanding of the composition of the lake for safety functionality.